2016
DOI: 10.1074/jbc.m116.714030
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the Sjögren-Larsson Syndrome Gene Aldh3a2 in Mice Increases Keratinocyte Growth and Retards Skin Barrier Recovery

Abstract: The fatty aldehyde dehydrogenase (FALDH) ALDH3A2 is the causative gene of Sjögren Larsson syndrome (SLS Sjögren-Larsson syndrome (SLS)2 is a hereditary neurocutaneous disorder caused by mutations in the fatty aldehyde dehydrogenase (FALDH) gene, ALDH3A2. The major symptoms of SLS are mental retardation, spastic di-or tetraplegia, and ichthyosis, with crystalline macular dystrophy sometimes comorbid (1). ALDH3A2 catalyzes the conversion of fatty aldehydes with medium-chain (MC) to very-long-chain fatty acids (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 55 publications
5
45
0
Order By: Relevance
“…In fact, we have previously identified similar defects in Aldh3a2 ‐knockout mice using this test . Aldh3a2 ‐knockout mice serve as a model for Sjögren‐Larsson syndrome, an autosomal recessive neurocutaneous disorder caused by mutations in the ALDH3A2 gene and characterized by spastic paraplegia and ichthyosis—symptoms also observed in patients with the ELOVL1 mutation. ALDH3A2 is a fatty aldehyde metabolizing enzyme, and Aldh3a2 ‐knockout mice exhibit a decrease in 2‐OH GalCer due to inactivation of FA2H, which synthesizes 2‐OH FAs for 2‐OH GalCer production .…”
Section: Discussionmentioning
confidence: 99%
“…In fact, we have previously identified similar defects in Aldh3a2 ‐knockout mice using this test . Aldh3a2 ‐knockout mice serve as a model for Sjögren‐Larsson syndrome, an autosomal recessive neurocutaneous disorder caused by mutations in the ALDH3A2 gene and characterized by spastic paraplegia and ichthyosis—symptoms also observed in patients with the ELOVL1 mutation. ALDH3A2 is a fatty aldehyde metabolizing enzyme, and Aldh3a2 ‐knockout mice exhibit a decrease in 2‐OH GalCer due to inactivation of FA2H, which synthesizes 2‐OH FAs for 2‐OH GalCer production .…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, ALDH3A2 −/− mice replicated some aspects of SLS symptoms, especially at the basal layer of the epidermis. Our results suggest that hyperproliferation of keratinocytes via oxidative stress responses may partly contribute to the ichthyosis symptoms of SLS . The ichthyosis is usually the first signal that brings the patient to medical attention, emphasizing the role of the dermatologist in the diagnosis.…”
Section: Genotype and Phenotype Relationship Between Aldh3a2 Mutationmentioning
confidence: 73%
“…The flow rate was 0.4 mL/min in the binary gradient system by using mobile phase A [acetonitrile/water (3:2, vol/vol) containing 10 mM ammonium formate] and mobile phase B [acetonitrile/2-pronanol (9:1, vol/vol) containing 10 mM ammonium formate]. The elution gradient steps were as follows: 0 min, 40% B; 0-18 min, gradient to 100% B; 18-23 min, 100% B; 23-23.1 min, gradient to 40% B; 23.1-25 min, 40% B. Lipids were detected by multiple reaction monitoring essentially as described (32) by selecting specific m/z at quadrupole mass filters Q1 and Q3 (Tables S1 and S2). Data were analyzed and quantified by using MassLynx software (Waters).…”
Section: Methodsmentioning
confidence: 99%
“…The Aldh3a2 deficiency causes a reduction in FALDH activity to ∼10% of wild-type CHO-K1 cells (31). We previously revealed that the metabolism of SPH and DHS to esterlinked glycerolipids was reduced in FAA-K1A cells and Aldh3a2 knockout (KO) keratinocytes; instead, SPH and DHS were unusually metabolized to ether-linked glycerolipids, plasmanylethanolamine/ plasmenylethanolamine (PlsE; plasmenylethanolamine, also known as ethanolamine plasmalogen) and plasmanylcholine (PlsC) (21,32). In those cells, unmetabolized fatty aldehydes are reduced to fatty alcohols and then incorporated into ether-linked glycerolipids (Fig.…”
Section: Aldh3a2 Ismentioning
confidence: 99%